Experimental design, modeling, and optimization of production of xylooligosaccharides by hydrothermal pretreatment of sugarcane bagasse and straw - Dias, Lídia Manfrin [UNESP]; Neto, Flávia Sanchez Penalva P. [UNESP]; Brienzo, Michel [UNESP]; de Oliveira, Samuel Conceição [UNESP]; Masarin, Fernando [UNESP] (Springer Nature, 2022)
Hydrothermal pretreatment (HP) of two by-products of sugarcane, bagasse (SB) and straw (SS), was optimized to produce xylooligosaccharides (XOS). A central composite rotational design (CCRD) in conjunction with response surface methodology was used to optimize the conditions for maximum XOS production. The developed mathematical models were statistically adequate to predict xylan conversion to XOS, and the by-products were promising for the production of XOS. For both by-products, the mass load in the optimal experiments was of 10%. The xylan conversion to XOS was 24.8% for SB and 45.3% for SS, XOS yield of 53.3 and 96 mg.g−1, respectively. The SB produced more XOS with a greater degree of polymerization than SS. Sugarcane by-products are important in the production of XOS, which may be a valuable commercial product. Furthermore, cellulose and lignin-enriched solids recovered following the optimized HP conditions can be fractionated to obtain other bioproducts of commercial interest.
Keywords: Central composite rotational design; Response surface methodology; Sugarcane by-products; Xylooligosaccharides production